2016
DOI: 10.3389/fnins.2016.00018
|View full text |Cite
|
Sign up to set email alerts
|

Potential Mechanisms Supporting the Value of Motor Cortex Stimulation to Treat Chronic Pain Syndromes

Abstract: Throughout the first years of the twenty-first century, neurotechnologies such as motor cortex stimulation (MCS), transcranial magnetic stimulation (TMS), and transcranial direct current stimulation (tDCS) have attracted scientific attention and been considered as potential tools to centrally modulate chronic pain, especially for those conditions more difficult to manage and refractory to all types of available pharmacological therapies. Interestingly, although the role of the motor cortex in pain has not been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
70
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(78 citation statements)
references
References 120 publications
(161 reference statements)
5
70
0
3
Order By: Relevance
“…The lower focality of TMS and tDCS, as compared to EBS, could make them less sensitive to relative mislocalizations around the targeted location. This difference could reconcile the relevance of our current findings with the fact that TMS and tDCS studies in perilesional stroke regions have generally reported beneficial therapeutic effects with potentially less variability than EBS studies (Lima and Fregni, 2008; O’Connell et al, 2014; Hosomi et al, 2015; DosSantos et al, 2016). …”
Section: Discussionsupporting
confidence: 57%
“…The lower focality of TMS and tDCS, as compared to EBS, could make them less sensitive to relative mislocalizations around the targeted location. This difference could reconcile the relevance of our current findings with the fact that TMS and tDCS studies in perilesional stroke regions have generally reported beneficial therapeutic effects with potentially less variability than EBS studies (Lima and Fregni, 2008; O’Connell et al, 2014; Hosomi et al, 2015; DosSantos et al, 2016). …”
Section: Discussionsupporting
confidence: 57%
“…66 More recent work has identified strong network connections between motor cortex and the peri-aqueductal gray (PAG), anterior cingulate cortex (ACC), and other critical pain matrix regions. 67 Proposed TMS neurophysiological mechanisms of action include activation of top-down pain inhibition pathways, 68 modulation of thalamocortical circuits 69 and changes in cortical excitability. 70 In addition to the treatment “specific” effects described above, rTMS for pain yields a particularly high placebo response.…”
Section: An Illustrative Examplementioning
confidence: 99%
“…Thus far, rTMS has been shown to be an effective treatment for burning mouth syndrome [191], complex regional pain syndrome [192], fibromyalgia [193,194], neuropathic pain [195,196,197], depressive disorders [198] and to a lesser degree PTSD and other anxiety disorders [199,200]. It has been proposed to prevent or revert the ongoing maladaptive plasticity within the pain matrix [201], and modify opioidergic, glutamatergic, gamma-aminobutyric acidergic, and serotoninergic neurotransmissions [202]. The application of screening, implementation of early interventions at the individual and familial level (e.g., teaching coping mechanisms, parent sensitivity training), refining current intervention strategies, and the innovation of new, targeted therapies, holds promise for addressing and reducing these comorbidities.…”
Section: Treatments For Comorbid Chronic Pain In Youthmentioning
confidence: 99%